The development of reading comprehension learning material by SQ4R strategy for grade iv at primary schools - Meiliza Sari; Sufyarma Marsidin; Darnis Arief (Fakultas Ilmu Pendidikan UNP)
Teachers have responsibility to create and develop an effective learning material in order to facilitate the student to understand the reading content optimally. There are, it is important to develop an effective learning material by using SQ4R strategy as the solution The type of this research is R&D by using 4-D model. The sample were 42 students and 2 teachers in primary school. The result of the research indicated that the validity rate of the learning material is valid. Then upon the assessment on the implementation of lesson plan, the responses from teachers and learning participants and the observations on teaching materials indicated that the practicality rate fell to the category of highly practical. Moreover, the result of the activity of learning participants on reading comprehension indicated to be effective. Hence, it could be concluded that the developed reading comprehension learning material by using SQ4R strategy has already been valid, practical, and effective.